Paleobiodiversity and large mammal associations during the Late Pliocene and the Early Pleistocene in South Africa: implications for hominin palaeoecology - (:unkn) unknown (My University, 2019)
We present a study of the evolution of large mammal associations during the Late Pliocene and the Early Pleistocene in South Africa. We show, based on factor analysis, the existence of at least three large mammal associations between 4.5 and 0.5 Ma with a large mammal turnover between 3.0 and 2.0 Ma. Furthermore, based on cluster analysis, a large mammal turnover between 2.61 and 2.4 is highlighted. Our results are consistent with the hypothesis of a faunal turnover around 2,5 Ma
Keywords: African Research